THE RELIABILITY AND CONSTRUCT VALIDITY OF SCORES ON THE ATTITUDES TOWARD PROBLEM SOLVING SCALE - Sabri Ahmad et al. (Proceedings of ICMSA, 2005)
The Attitudes Toward Problem Solving Scale (ATPSS) has received limitedattention concerning its reliability and validity with a Malaysian secondaryeducation population. Developed by Charles, Lester O'Daffer (1987), theinstruments assessed attitudes toward problem solving in areas of Willingness to Engage in Problem Solving Activities, Perseverance During the Problem Solving Process and Self Confidence With Respect to Problem Solving. This study addressed the lack of information about this measure by examining the scale's reliability and its factorial structure. Subjects were 233 secondary schoolstudents. Reliability coefficients of the three subscales and the total score werehigh, indicating that the scale is stable and reliable in measuring AttitudesToward Problem Solving. Results from factor analyses imply that the ATPSSmeasures more various traits in Malaysian culture.Key words: Attitudes toward problem solving, reliability, validity